Effects of planting distance and weeding regime on green bean (Phaseolus vulgaris L.) growth and yield - Feizollah, Jamali; Aminpanah, Hashem (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2017)
Manipulation in planting distance can increase crop growth and yield by increasing radiation interception and minimizing intra- and inter-specific competition. To evaluate the effect of planting distance and weeding regime on green bean yield (Phaseolus vulgaris L.), an experiment was conducted as a randomized complete block in a factorial arrangement with three replicates in Ramsar, northern Iran, in 2013. The study factors were planting distance (30 x 30 cm, 40 x 20 cm and 50 x 20 cm), and weeding [a manual weeding, two weeding by hand, and weed control (not eliminated during whole period of crop growth)]. Analysis of variance showed that the main effects of planting distance and weeding regime were significant on green pod yield (P£0.01), while the interaction between them was not significant. Moreover, main effect of weeding regime was significant for weed dry biomass, while the main effect of planting distance and interaction between them were not significant. Mean comparison indicated that the highest and the lowest green pod yield were recorded for planting distances of 40 x 20 cm and 30 x 30 cm, respectively. Moreover, the highest green pod yield was recorded for two hand weedings, while the lowest ones were recorded for un-weeded plots. At the same time, the highest and the lowest weed dry biomass were recorded for un-weeded plots and plots with two hand weedings, respectively. In conclusion, planting distance of 40× 20 cm and two hand weeding during the crop growing period are recommended to get the highest fresh green bean pods por are recommended to get the highest fresh green bean pods.